Keanekaragaman Jenis Suku Rubiaceae di Taman Wisata Alam Pananjung Pangandaran - Nabila, Aura; Ruhhayani, Siti; Alvianti, Mutiara Dwi; Riyanni, Cahya Sukma; Wijaya, Agung; Muliyah, Evi (Symbiotic: Journal of Biological Education and Science, 2025)
Pananjung Pangandaran Nature Tourism Park (TWA) is a lowland tropical rainforest ecosystem renowned for its high biodiversity. This study aims to analyze the diversity of plant species from the Rubiaceae family within the TWA Pangandaran area. The research employed a direct exploration method (Cruise Method) by surveying existing footpaths throughout the park. Every encountered Rubiaceae plant was recorded and documented, accompanied by measurements of environmental parameters including temperature, humidity, light intensity, and wind speed. The study successfully identified 4 species from the Rubiaceae family: Psychotria asiatica, Hypobathrum racemosum, Nauclea pallida, and Coffea sp., with a total of 266 individuals. Psychotria asiatica was the most dominant species, with 188 individuals recorded. The area exhibited neutral soil pH (6.5-7.0), air temperature ranging from 28.7-31.0°C, air humidity between 73.7-87.2%, and light intensity levels of 51-113 lux. Species composition and individual distribution varied across the different observation trails. The findings of this study are expected to serve as fundamental data for conservation efforts and biodiversity management within the TWA Pangandaran area